Analysis of Public Relations Strategy of Bogor Regency Communication and Information Office in Disseminating the Pancakarsa Program Case Study of Gunung Putri District - Martha, Layung Paramesti; Prasetyo, Danang (UNIVERSITAS PAKUAN, 2023)
This study aims to explain the public relations strategy of the Bogor Regency Diskominfo in the Socialization of the PANCAKARSA Program with a case study of Gunung Putri District. in the socialization activities of the PANCAKARSA Program involving the Public Relations of the Communication and Information Office of Bogor and Gunung Putri District. This research method uses a qualitative description with data collection, interviews with key informants and informants and documentation. as for the data analysis techniques carried out by data reduction, data presentation, and drawing conclusions. The data validity technique in this study used the triangulation method. The technique used to answer the problem is using a public relations strategy to make decisions about program goals and objectives, identify audiences, establish policies or rules to determine the chosen strategy, decide which strategy to use. Based on the results of the research on the Public Relations Strategy of the Bogor Regency Diskominfo in disseminating the PANCAKARSA Program as a whole it was good and the strategies used in the socialization were: disseminating information through existing media such as websites, Social Media, Banners, Innovation Magazines, Radio, Videotron, DSP and other media. digital and print